A review of the hexapod tracheal system with a focus on the apterygote groups. (July 2021) - Dittrich, Kathleen; Wipfler, Benjamin
Abstract: Respiratory systems are key innovations for the radiation of terrestrial arthropods. It is therefore surprising that there is still a considerable lack of knowledge. In this review of the available information on tracheal systems of hexapods (with a focus on the apterygote lineages Protura, Collembola, Diplura, Archaeognatha and Zygentoma), we summarize available data on the spiracles (number, position and morphology), the shape and variability of tracheal branching patterns including anastomoses, the tracheal fine structure and the respiratory proteins. The available data are strongly fragmented, and information for most subgroups is missing. In various cases, individual observations for one species account for the knowledge of the entire order. The available data show that there are strong differences between but also within apterygote orders. We conclude that the available data are insufficient to derive detailed conclusions on the hexapod ground plan and outline the possible evolutionary scenarios for the tracheal system in this group. Highlights: The knowledge on the tracheal systems of the hexapods with a focus on the primary wingless groups is compiled. Available knowledge is very fragmentary and in many cases individual observations on single species account for an entire order. Hypotheses for the hexapod ground plan are presented but the available data are insufficient to favor one of them. Speculations or hypotheses about the evolution of the hexapod tracheal system should be avoided before more data are available. Further research is indispensable to understand the evolutionary processes that led to the variety of tracheal systems.